1996
DOI: 10.1136/thx.51.5.516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-arginine on renal blood flow in normal subjects and patients with hypoxic chronic obstructive pulmonary disease.

Abstract: Background -L-arginine is the precursor of endothelium derived nitric oxide (NO) and increasing the available substrate may increase the production of NO. This has been shown by local infusion in peripheral vascular beds but there are few studies of the effects during systemic infusion. Renal vasoconstriction is known to be important in the pathogenesis of cor pulmonale in patients with hypoxic chronic obstructive pulmonary disease (COPD). The effects of a systemic infusion of L-arginine on renal and aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
0
14
2
Order By: Relevance
“…Supporting a possible limitation by L-arginine, L-arginine supplementation raised NO production (8) and decreased hypoxic pulmonary vasoconstriction and pulmonary vascular remodeling in chronically hypoxic rats (21). Effects of L-arginine supplementation are not limited to the pulmonary circulation, as shown by increased renal blood flow after systemic L-arginine infusion (13). Chronic hypoxia has been shown to impair L-arginine uptake (8), suggesting that this may be one mechanism by which chronic hypoxia might limit NO production.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Supporting a possible limitation by L-arginine, L-arginine supplementation raised NO production (8) and decreased hypoxic pulmonary vasoconstriction and pulmonary vascular remodeling in chronically hypoxic rats (21). Effects of L-arginine supplementation are not limited to the pulmonary circulation, as shown by increased renal blood flow after systemic L-arginine infusion (13). Chronic hypoxia has been shown to impair L-arginine uptake (8), suggesting that this may be one mechanism by which chronic hypoxia might limit NO production.…”
Section: Discussionmentioning
confidence: 95%
“…Administration of the nonspecific NO synthase (NOS) inhibitor nitro-L-arginine (NLA) eliminated the difference in contractile sensitivity between the vessels from the normoxic and chronically hypoxic animals, suggesting that reduction in NO production and/or activity was responsible for the increased contractile sensitivity observed. Because cofactors for NOS are not saturating in the cerebral circulation (25) and dietary supplementation with L-arginine has been shown to at least partially reverse hypoxia-associated increases in contractile responsiveness in other circulations (13,21), we reasoned that dietary supplementation with L-arginine might restore NO production and/or activity and thereby reduce contractile sensitivity in vessels from chronically hypoxic animals to normoxic values. Results indicated that this did not occur, suggesting that other factors served to reduce NO production and augment MCA contractility under conditions of chronic hypoxia.…”
mentioning
confidence: 99%
“…There is evidence in the literature to support both possibilities. On the one hand, endothelial function appears to be abnormal in smokers (24,25) and in patients with COPD (26,27). On the other, the number of peripheral capillaries appears to be reduced in COPD (28).…”
Section: Discussionmentioning
confidence: 96%
“…When hypercapnia complicates COPD, the vasodilatory responses to dopamine [30], L-arginine [33], protein loading [34] and even oxygen [30] are lost. Whether this means that structural changes make the renal vasculature less responsive, is not known.…”
Section: Renal Haemodynamics and Tubular Functionmentioning
confidence: 99%